A retrospective observational study on effect of sperm morphology on embryo development after intracytoplasmic sperm injection - Yaramareddy, Swapna; Babu Valluri, Lenin; S. Gottipati, Satheesh; Naik Bhukya, Nom Kumar; Sardena, Siyonu Kumari; Naik Menavath, Tulasi Ram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The process of embryo development requires the contribution of both male and female gametes. However, abnormal sperm development can hinder the fertilization process, leading to infertility. To overcome these male fertility issues, intracytoplasmic sperm injection (ICSI) was developed. This technique has proven to be effective, resulting in about 80% of live births in ICSI cycles. Methods: It is a retrospective cohort study was conducted in department of reproductive medicine, Komali fertility centre a unit of Dr. Ramesh Cardiac and multispeciality hospital P Ltd, Guntur, Andhra Pradesh, India. The study was conducted during period of January 2022 to December 2022. Total 120 subjects were included based on our inclusion and exclusion criteria. Results: This study used the chi-square test and Pearson’s correlation to evaluate the relationship between sperm morphology and various parameters, revealing that poor sperm morphology may contribute to low fertilization, cleavage, and pregnancy outcomes. Individuals with 3% sperm morphology exhibited higher mean fertility rates and lower negative pregnancy rates compared to those with 2% and 1% morphology, highlighting the importance of good sperm morphology for successful fertilization and pregnancy outcomes. Conclusions: In summary, the study highlights a strong correlation between sperm morphology, fertilization and cleavage rates, while a weak and no correlation was observed between sperm morphology and pregnancy outcome after ICSI. The findings suggest that an improvement in sperm morphology leads to increased fertilization and cleavage rates.